Method for producing conductive particles and conductive particles
By heating the conductive particles under high vacuum, the problem of the conductive layer reacting with the residual components of the reaction liquid at high temperature in the prior art is solved, and high performance and low manufacturing cost of the conductive particles are achieved.
Patent Information
- Application Number
- CN202180036693.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-01-19
- Filing Date
- 2021-05-18
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2041-05-18
AI Technical Summary
When the prior art heat treatment of conductive particles, it is easy to react with the metal of the reaction liquid with the conductive part, making it difficult to obtain the desired properties, and at the same time, the use of inactive gas increases the manufacturing cost.
Heating treatment under high vacuum promotes metal crystallization of the conductive layer and reduces the impact on the quality of conductive particles.
Through high vacuum heating treatment, defects of the conductive layer are reduced, uniformity is improved, and deterioration of quality is suppressed, and conductive particles with excellent current resistance, low connection resistance and high connection reliability are obtained.
Smart Images

Figure CN115667579B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a method for producing conductive particles and the conductive particles. Background Art
[0002] Conductive particles used as conductive materials for anisotropic conductive materials such as anisotropic conductive films or anisotropic conductive pastes are generally known to have a conductive layer made of metal formed on the surface of a core particle, and electrical connection between electrodes or wiring is performed through the conductive layer. As the conductive layer of the conductive particles, a nickel-plated film obtained by an electroless plating method is often used.
[0003] The nickel-plated film obtained by the electroless plating method contains phosphorus precipitated from the reducing agent as an impurity, so it forms a film containing a large amount of amorphous. Therefore, a technology is disclosed for improving various properties of the conductive layer by crystallizing the nickel-plated film by heating the conductive particles.
[0004] For example, Patent Document 1 describes that the powder for forming a nickel coating is heat treated in an inert gas atmosphere or a slightly reducing atmosphere at 300 to 600°C to adjust the crystallite diameter of the nickel structure constituting the nickel coating, thereby improving the adhesion stability with the gold coating applied after the process. It is disclosed that the conductor obtained by using a two-layer coating particle powder of nickel and gold has a low resistance value.
[0005] Patent Document 2 also discloses that the number of hydrogen atoms in the conductive part is reduced by annealing the conductive particles at 200°C or higher, thereby producing conductive particles with a conductive part having a crystallite size of 50 nm or higher. This effect discloses that cracking of the conductive part can be suppressed, and acid resistance is improved, thereby providing excellent connection reliability.
[0006] Prior art literature
[0007] Patent Literature
[0008] Patent Document 1: Japanese Patent Application Publication No. 2005-200728
[0009] Patent Document 2: Japanese Patent Application Publication No. 2016-167449 Summary of the invention
[0010] Technical problem to be solved by the invention
[0011] However, although the heat treatment of the conductive particles can adjust the crystallites of the metal in the conductive part, since the conductive particles are exposed to high temperature, the residual components of the reaction solution used in forming the conductive layer react with the metal in the conductive part, and it is difficult to obtain conductive particles with the desired performance. In addition, the use of inert gas such as nitrogen or argon during the heat treatment increases the manufacturing cost, which is not economical.
[0012] Therefore, an object of the present invention is to provide a method for producing conductive particles which has little influence on the quality of the conductive particles and can reduce the production cost.
[0013] Technical solutions for solving technical problems
[0014] In order to solve the above technical problems, the inventors of the present invention have conducted intensive research and found that when the conductive particles are heated, the crystallization of the metal of the conductive layer is promoted by heating under a high vacuum, and the influence on the quality of the conductive particles is reduced. Specifically, it is found that by heating under a high vacuum, the defects of the conductive layer are reduced, the uniformity is improved, and the quality degradation can be suppressed, so that the conductive particles have excellent current tolerance, low connection resistance, and excellent connection reliability, thereby completing the present invention.
[0015] That is, the present invention provides a method for producing conductive particles, comprising the step of heating conductive particles having a conductive layer on the surface of core particles at a temperature of 200 to 600° C. under a vacuum of 1000 Pa or less.
[0016] The present invention also provides conductive particles having a conductive layer formed on the surface of a core particle, wherein the average withstand current value of each conductive particle at a compression rate of 30% is 200 mA or more.
[0017] Effects of the Invention
[0018] According to the present invention, it is possible to provide conductive particles having excellent current resistance, low connection resistance, and excellent connection reliability, and a method for producing the conductive particles. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 This is a SEM image of the conductive particles obtained in Example 1. DETAILED DESCRIPTION
[0020] Hereinafter, preferred embodiments of the method for producing the conductive particles of the present invention will be described.
[0021] The method for producing conductive particles of the present invention includes a vacuum heating step of heating conductive particles having a conductive layer on the surface of core particles at a temperature of 200 to 600° C. under a vacuum of 1000 Pa or less.
[0022] Hereinafter, the conductive particles having a conductive layer on the surface of the core particles to be subjected to the above-mentioned vacuum heating step will be described.
[0023] The conductive particles are conductive particles in which a conductive layer is formed on the surface of a core particle.
[0024] As the above-mentioned core material particles, as long as they are granular, whether inorganic or organic, they can be used without particular restrictions. As the core material particles of inorganic matter, metal particles, alloys, glass, ceramics, silicon dioxide, metal or non-metallic oxides (also including hydrates) of gold, silver, copper, nickel, palladium, solder, etc., metal silicates including aluminosilicates, metal carbides, metal nitrides, metal carbonates, metal sulfates, metal phosphates, metal sulfides, metal acid salts, metal halides and carbon, etc. can be listed. On the other hand, as the core material particles of organic matter, for example, thermoplastic resins such as natural fibers, natural resins, polyethylene, polypropylene, polyvinyl chloride, polystyrene, polybutene, polyamide, polyacrylate, polyacrylonitrile, polyacetal, ionomers, polyesters, alkyd resins, phenolic resins, urea resins, benzoguanamine resins, melamine resins, xylene resins, silicone resins, epoxy resins, thermosetting resins such as diallyl phthalate resins can be listed. These can be used alone, or two or more can be used in combination.
[0025] The core particles may also be composed of a material containing both inorganic and organic substances, instead of being composed of a material containing either of the above-mentioned inorganic and organic substances. In the case where the core particles are composed of a material containing both inorganic and organic substances, the existence of inorganic and organic substances in the core particles may include, for example, a core composed of an inorganic substance and a shell composed of an inorganic substance covering the surface of the core; or a core composed of an organic substance and a shell composed of an inorganic substance covering the surface of the core, etc., such as a core-shell type structure. In addition to these, a structure in which inorganic and organic substances are mixed in one core particle, or a randomly fused mixed type structure may also be mentioned.
[0026] The core particles are preferably composed of a material comprising both organic or inorganic and organic substances, and more preferably composed of a material comprising both inorganic and organic substances. The above-mentioned inorganic substances are preferably glass, ceramics, silicon dioxide, metal or non-metal oxides (also including hydrates), metal silicates including aluminosilicates, metal carbides, metal nitrides, metal carbonates, metal sulfates, metal phosphates, metal sulfides, metal acid salts, metal halides and carbon. In addition, the above-mentioned organic substances are preferably thermoplastic resins such as natural fibers, natural resins, polyethylene, polypropylene, polyvinyl chloride, polystyrene, polybutene, polyamide, polyacrylate, polyacrylonitrile, polyacetal, ionomers, polyesters. By using a core material composed of such a material, the dispersion stability of the particles can be improved, and when the electronic circuit is electrically connected, appropriate elasticity can be shown to improve conduction.
[0027] In order to easily maintain the shape of the core particles and to easily maintain the shape of the core particles in the process of forming the metal coating, when an organic substance is used as the core particle, it is preferred that the core particle has no glass transition temperature or has a glass transition temperature exceeding 100° C. The glass transition temperature can be obtained, for example, as the intersection of the original baseline of the baseline shift portion of the DSC curve obtained by differential scanning calorimetry (DSC) and the tangent line of the inflection point.
[0028] When an organic substance is used as the core particle, when the organic substance is a highly cross-linked resin, even if the glass transition temperature is measured to 200°C using the above method, almost no baseline shift is observed. In this specification, such particles are also referred to as particles without a glass transition temperature, and such core particles can be used in the present invention. As a specific example of a core particle material without a glass transition temperature, a cross-linking monomer and a monomer constituting the organic substance exemplified above can be used together to copolymerize them to obtain the core particle. Examples of the crosslinking monomer include tetramethylene di(meth)acrylate, ethylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, ethylene oxide di(meth)acrylate, tetraethylene oxide (meth)acrylate, 1,6-hexane di(meth)acrylate, neopentyl glycol di(meth)acrylate, 1,9-nonanediol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, tetramethylolmethane di(meth)acrylate, tetramethylolmethane tri(meth)acrylate, and tetramethylolpropane tri(meth)acrylate. Multifunctional (meth)acrylates such as hydroxymethylmethane tetra(meth)acrylate, tetramethylolpropane tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, glycerol di(meth)acrylate, glycerol tri-di(meth)acrylate, multifunctional vinyl monomers such as divinylbenzene and divinyltoluene, silane-containing monomers such as vinyltrimethoxysilane, trimethoxysilylstyrene, and γ-(meth)acryloxypropyltrimethoxysilane, triallyl isocyanurate, diallyl phthalate, diallyl acrylamide, and diallyl ether. In particular, in the field of COG (chip on glass), core particles formed of such hard organic materials are often used.
[0029] The shape of the core particles is not particularly limited. The core particles are usually spherical. However, the core particles may also be in shapes other than spherical, such as fibrous, hollow, plate-like or needle-like, and may also have a plurality of protrusions on the surface, or be amorphous. In the present invention, spherical core particles are preferred from the perspective of excellent filling properties and easy metal coating.
[0030] The conductive layer formed on the surface of the core material particles is composed of a metal with conductivity. As the metal constituting the conductive layer, for example, metals such as gold, platinum, silver, copper, iron, zinc, nickel, tin, lead, antimony, bismuth, cobalt, indium, titanium, germanium, aluminum, chromium, palladium, tungsten, molybdenum, calcium, magnesium, rhodium, sodium, iridium, beryllium, ruthenium, potassium, cadmium, osmium, lithium, rubidium, gallium, thallium, tantalum, cesium, thorium, strontium, polonium, zirconium, barium, manganese or their alloys, and metal compounds such as ITO and solder, etc. can be listed. Among them, gold, silver, copper, nickel, palladium, rhodium or solder are preferred because of their small resistance, and are particularly suitable for using nickel, gold, nickel alloy or gold alloy. The metal can be one, or two or more can be used in combination.
[0031] The conductive layer may be a single layer structure or a laminated structure consisting of multiple layers. In the case of a laminated structure consisting of multiple layers, the outermost layer is preferably at least one selected from nickel, gold, silver, copper, palladium, nickel alloys, gold alloys, silver alloys, copper alloys and palladium alloys.
[0032] Furthermore, the conductive layer may not cover the entire surface of the core particle, but may cover only a portion thereof. When only a portion of the surface of the core particle is covered, the covered portion may be continuous or may be discontinuously covered in an island shape, for example.
[0033] The thickness of the conductive layer is preferably from 0.1 nm to 2000 nm, more preferably from 1 nm to 1500 nm. When the thickness of the conductive layer is within the above range, conductive particles with excellent electrical properties can be obtained. In the case where the conductive particles have protrusions described later, the height of the protrusions is not included in the thickness of the conductive layer mentioned here. In the present invention, the thickness of the conductive layer can be measured by cutting the particle to be measured into two halves and observing the cross section of the cut using a scanning electron microscope (SEM).
[0034] The average particle size of the conductive particles is preferably not less than 0.1 μm and not more than 50 μm, and more preferably not less than 1 μm and not more than 30 μm. When the average particle size of the conductive particles is within the above range, short circuits will not occur in directions different from those between the opposing electrodes, and conduction between the opposing electrodes can be easily ensured. In the present invention, the average particle size of the conductive particles is a value measured by SEM observation. Specifically, the average particle size of the conductive particles can be measured by the method described in the embodiments. The particle size is the diameter of a circular conductive particle image. In the case where the conductive particles are not spherical, the particle size refers to the maximum length (maximum length) in a line segment that crosses the conductive particle image.
[0035] In the case where the conductive particles have protrusions on their surfaces, that is, when the outer surface of the conductive layer is in the shape of a protrusion, the height of the protrusion is preferably 20 nm or more and 1000 nm or less, and more preferably 50 nm or less and 800 nm or less. The number of protrusions also varies depending on the particle size of the conductive particles. From the perspective of further improving the conductivity of the conductive particles, it is advantageous to have 1 or more and 20,000 or less, and more preferably 5 or more and 5,000 or less, in each conductive particle. In addition, the length of the base of the protrusion is preferably 5 nm or more and 1000 nm or less, and more preferably 10 nm or more and 800 nm or less. When the cross section of the particle is observed by SEM, the length of the base of the protrusion refers to the length of the surface of the conductive particle at the site where the protrusion is formed, and the height of the protrusion refers to the shortest distance from the base of the protrusion to the vertex of the protrusion. Among them, in the case where a protrusion has multiple vertices, the highest vertex is taken as the height of the protrusion. The length of the base of the protrusion and the height of the protrusion are the arithmetic mean of the values measured for 20 different particles observed using an electron microscope.
[0036] The shape of the conductive particles also varies depending on the shape of the core particles, and there is no particular limitation. For example, the conductive particles may be fibrous, hollow, plate-like, or needle-like, or may have a plurality of protrusions on the surface, or may be amorphous. In the present invention, from the perspective of excellent filling and connectivity, the conductive particles may preferably be spherical or have a plurality of protrusions on the outer surface.
[0037] As a method for forming a conductive layer on the surface of the core material particle, there can be listed dry methods using vapor deposition, sputtering, mechanochemical method, mixing method, etc., and wet methods using electrolytic plating method, electroless plating method, etc. In addition, these methods can also be combined to form a conductive layer on the surface of the core material particle.
[0038] In the present invention, in order to easily obtain conductive particles having desired particle properties, it is preferred to form a conductive layer on the surface of the core particles by electroless plating. It is particularly preferred that the conductive particles have an electroless nickel-phosphorus plating layer formed on the surface of the core particles as the conductive layer.
[0039] Hereinafter, a case where a nickel-phosphorus plating layer is formed as the conductive layer will be described.
[0040] When a conductive layer is formed on the surface of the core material particle by an electroless plating method, the core material particle preferably has the ability to capture precious metal ions on its surface, or is surface-modified so that it has the ability to capture precious metal ions. The precious metal ions are preferably ions of palladium or silver. Having the ability to capture precious metal ions means that the precious metal ions can be captured in the form of a chelate or a salt. For example, when there are amino groups, imino groups, amide groups, imide groups, cyano groups, hydroxyl groups, nitrile groups, carboxyl groups, etc. on the surface of the core material particle, the surface of the core material particle has the ability to capture precious metal ions. In the case of surface modification to make it have the ability to capture precious metal ions, for example, the method described in Japanese Patent Gazette No. 61-64882 can be used.
[0041] Such core particles are used to carry precious metals on their surfaces. Specifically, the core particles are dispersed in a dilute acidic aqueous solution of a precious metal salt such as palladium chloride or silver nitrate. Thus, the surface of the particles captures precious metal ions. The concentration of the precious metal salt is 100% relative to 1 m 2 The surface area is 1×10 -7 ~1×10 -2 The molar range is sufficient. The core particles that have captured the precious metal ions are separated from the system and washed with water. Next, the core particles are suspended in water, a reducing agent is added thereto, and the precious metal ions are reduced. Thus, the surface of the core particles is loaded with precious metals. The reducing agent can be, for example, sodium hypophosphite, sodium borohydride, potassium borohydride, dimethylamine borane, hydrazine, formaldehyde, etc., preferably selected from these based on the constituent materials of the target conductive layer.
[0042] Before the core particles are made to capture precious metal ions, a sensitization treatment may be performed to adsorb tin ions on the particle surfaces. For example, the surface-modified core particles may be placed in an aqueous solution of stannous chloride and stirred for a predetermined time to adsorb tin ions on the particle surfaces.
[0043] The core particles subjected to the pretreatment are subjected to a conductive layer forming treatment. There are two types of conductive layer forming treatment: a treatment for forming a conductive layer having protrusions and a treatment for forming a conductive layer having a smooth surface. First, the treatment for forming a conductive layer having protrusions will be described.
[0044] In the process of forming the conductive layer having the protrusions, the following first step and second step are performed.
[0045] The first step is an electroless nickel plating step of mixing an aqueous slurry of core particles with an electroless nickel plating bath containing a dispersant, a nickel salt, a reducing agent, a ligand, etc. In such a first step, while forming a conductive layer on the core particles, the plating bath self-decomposes. The self-decomposition occurs near the core particles, so when the conductive layer is formed, the self-decomposition products are captured on the surface of the core particles, thereby generating the core of the micro-protrusions, and at the same time forming the conductive layer. The protrusions grow based on the core of the generated micro-protrusions.
[0046] In the first step, the aforementioned core material particles are fully dispersed in water in a range of preferably 0.1 to 500 g / L, more preferably 1 to 300 g / L to prepare an aqueous slurry. The dispersion operation can be performed using conventional stirring, high-speed stirring, or a shearing dispersion device such as a colloid mill or a homogenizer. In addition, ultrasound can also be used in the dispersion operation. As needed, a dispersant such as a surfactant is sometimes added in the dispersion operation. Next, an aqueous slurry of the core material particles subjected to the dispersion operation is added to an electroless nickel plating bath containing a nickel salt, a reducing agent, a ligand, and various additives, and the first step of electroless plating is performed.
[0047] As the aforementioned dispersant, for example, nonionic surfactants, zwitterionic surfactants and / or water-soluble polymers can be cited. As nonionic surfactants, polyoxyalkylene ether surfactants such as polyethylene glycol, polyoxyethylene alkyl ether, polyoxyethylene alkylphenyl ether, etc. can be used. As zwitterionic surfactants, betaine surfactants such as alkyl dimethyl acetate betaine, alkyl dimethyl carboxymethyl acetate betaine, alkyl dimethyl amino acetate betaine can be used. As water-soluble polymers, polyvinyl alcohol, polyvinyl pyrrolidone, hydroxyethyl cellulose, etc. can be used. These dispersants can be used alone or in combination of two or more. The amount of dispersant used also varies depending on its type, and is usually 0.5 to 30 g / L relative to the volume of the liquid (electroless nickel plating bath). In particular, from the viewpoint of further improving the adhesion of the conductive layer, it is preferred that the amount of dispersant used is in the range of 1 to 10 g / L relative to the volume of the liquid (electroless nickel plating bath).
[0048] As the nickel salt, for example, nickel chloride, nickel sulfate or nickel acetate can be used, and its concentration is preferably in the range of 0.1 to 50 g / L. As the reducing agent, for example, the same reducing agent as the above-mentioned reducing agent for reducing the noble metal ions can be used, and it is selected based on the constituent material of the target base film. When a phosphorus compound such as sodium hypophosphite is used as the reducing agent, its concentration is preferably in the range of 0.1 to 50 g / L.
[0049] As a coordination agent, for example, carboxylic acids (salts) such as citric acid, glycolic acid, tartaric acid, malic acid, lactic acid, gluconic acid or their alkali metal salts or ammonium salts, amino acids such as glycine, ethylenediamine, alkylamines, other ammonium, EDTA or pyrophosphate (salts) and other compounds that have a coordination effect on nickel ions can be used. These can be used alone or in combination of two or more. The concentration is preferably in the range of 1 to 100 g / L, more preferably in the range of 5 to 50 g / L. The preferred pH of the electroless nickel plating bath at this stage is in the range of 3 to 14. The electroless nickel plating reaction starts rapidly when the aqueous slurry of the core particles is added, accompanied by the generation of hydrogen. The moment when the hydrogen generation is completely invisible is regarded as the end of the first process.
[0050] Then, in the second step, following the first step, (i) a first aqueous solution containing one of a nickel salt, a reducing agent and an alkali, and a second aqueous solution containing the remaining two, or (ii) a first aqueous solution containing a nickel salt, a second aqueous solution containing a reducing agent and a third aqueous solution containing an alkali are used, and these aqueous solutions are added to the liquid of the first step simultaneously and over time to perform electroless nickel plating. When these liquids are added, the plating reaction is started again, and by adjusting the amount added, the conductive layer formed can be controlled to a desired film thickness. After the addition of the electroless nickel plating solution is completed, after the generation of hydrogen is completely invisible, the liquid temperature is temporarily maintained and stirring is continued to terminate the reaction.
[0051] In the case of (i) above, it is preferred to use a first aqueous solution containing a nickel salt and a second aqueous solution containing a reducing agent and an alkali, but the combination is not limited thereto. In this case, the first aqueous solution does not contain a reducing agent and an alkali, and the second aqueous solution does not contain a nickel salt. As the nickel salt and the reducing agent, the above-mentioned substances can be used. As the alkali, for example, an alkali metal hydroxide such as sodium hydroxide or potassium hydroxide can be used. The same is true for the case of (ii) above.
[0052] In the case of (ii) above, the first to third aqueous solutions contain a nickel salt, a reducing agent, and an alkali, respectively, and each aqueous solution does not contain two components other than these components.
[0053] In any of the cases (i) and (ii), the concentration of the nickel salt in the aqueous solution is preferably 10 to 1000 g / L, particularly preferably 50 to 500 g / L. Regarding the concentration of the reducing agent, when a phosphorus compound is used as the reducing agent, it is preferably 100 to 1000 g / L, particularly preferably 100 to 800 g / L. When a boron compound is used as the reducing agent, it is preferably 5 to 200 g / L, particularly preferably 10 to 100 g / L. When hydrazine or a derivative thereof is used as the reducing agent, it is preferably 5 to 200 g / L, particularly preferably 10 to 100 g / L. The concentration of the base is preferably 5 to 500 g / L, particularly preferably 10 to 200 g / L.
[0054] The second step is performed continuously after the first step is completed, but the first step and the second step may be performed intermittently instead of this. In this case, the second step may be performed after the first step is completed, in which the core particles and the plating solution are separated by filtering or the like, and then the core particles are dispersed in water, and an aqueous slurry is prepared again, and an aqueous solution in which a complexing agent is dissolved in a concentration range of preferably 1 to 100 g / L, more preferably 5 to 50 g / L, is added thereto, and a dispersant is dissolved in a range of preferably 0.5 to 30 g / L, more preferably 1 to 10 g / L, to prepare an aqueous slurry, and then the above-mentioned aqueous solutions are added to the aqueous slurry. In this way, a conductive layer with protrusions can be formed.
[0055] Next, a process for forming a conductive layer having a smooth surface will be described below.
[0056] The formation of the conductive layer with a smooth surface can be performed by reducing the concentration of the nickel salt in the electroless nickel plating bath in the first step of the process for forming the conductive layer with protrusions. That is, as the nickel salt, for example, nickel chloride, nickel sulfate or nickel acetate can be used, and the concentration is preferably in the range of 0.01 to 0.5 g / L. By performing the above-mentioned first step and second step by only reducing the concentration of the nickel salt in the electroless nickel plating bath, a conductive layer with a smooth surface can be formed.
[0057] In this manner, conductive particles to be used in the vacuum heating step of the present invention can be obtained.
[0058] The vacuum degree of the vacuum heating process of the present invention is less than 1000Pa, preferably 0.01 to 900Pa, and particularly preferably 0.01 to 500Pa. By making the vacuum degree within this range, the residual components of the reaction solution used when forming the conductive layer can be smoothly removed. Therefore, even at high temperatures, the metal of the conductive layer is unlikely to undergo side reactions, and conductive particles with excellent desired characteristics such as connection reliability can be obtained. As long as the above-mentioned effects are not hindered, the vacuum heating process can be implemented at a certain vacuum degree, or by changing the vacuum degree. For example, when the vacuum degree is reduced, the change in the vacuum degree can be carried out by adding an inert gas such as nitrogen or argon. In addition, when the vacuum degree is increased, it can be carried out by increasing the output of the vacuum pump. Among them, the vacuum degree in the present invention is an absolute pressure, that is, the value when the absolute vacuum is set to 0.
[0059] The heating temperature in the vacuum heating step of the present invention is 200 to 600° C., preferably 250 to 500° C., and particularly preferably 300 to 450° C. When the heating temperature is within this range, crystallization of the metal of the conductive layer is promoted, thereby reducing resistance and improving electrical conductivity.
[0060] The heating rate from room temperature to the heating temperature in the vacuum heating step of the present invention is preferably 0.1 to 50°C / min, more preferably 0.1 to 30°C / min. By adopting this heating rate, the crystallization of the metal of the conductive portion is smoothly promoted, so that the resistance becomes low and the electrical conductivity is excellent.
[0061] The cooling rate of the vacuum heating process of the present invention is preferably 0.02 to 50°C / min, more preferably 0.02 to 30°C / min. It is preferred that the cooling rate until at least 50°C is within this range. The cooling rate can be controlled by placing room temperature or cooled gas or by cooling the heating furnace shell with cooling water or the like. By adopting this cooling rate, the modification of the core particles or the conductive layer due to the heat experience can be suppressed, thereby reducing the impact on the quality.
[0062] The treatment time of the vacuum heating process of the present invention is preferably 0.1 to 10 hours, more preferably 0.5 to 5 hours. By adopting this treatment time, the manufacturing cost can be reduced, and the modification of the core particles or the conductive layer due to heat experience can be suppressed, reducing the impact on quality. Among them, the treatment time refers to the time for heating within the above-mentioned heating temperature range.
[0063] The vacuum heating process of the present invention can be performed while the conductive particles are left to stand, or can be performed while stirring. When the vacuum heating process is performed while the conductive particles are left to stand, it is preferred that the conductive particles be left to stand at a thickness of 0.1 mm to 100 mm. By leaving the conductive particles to stand at this thickness, the conductive layer can be vacuum heated smoothly, and the manufacturing cost can be reduced.
[0064] The vacuum heating process of the present invention is to heat the container containing the conductive particles in a static state after evacuating the container, or to heat the container while stirring. At this time, the vacuuming may be performed after replacing the gas phase of the container containing the conductive particles with an inert gas such as nitrogen, or the vacuuming may be performed directly. In addition, the vacuum heating process of the present invention may be repeated multiple times as needed.
[0065] Next, the conductive particles of the present invention will be described.
[0066] Regarding the conductive particles of the present invention, the average withstand current value of one conductive particle is 200 mA or more, and particularly preferably 300 mA or more. By making the average withstand current value of one conductive particle within the above range, the connection resistance becomes low and the connection reliability is excellent. Considering that a large withstand current value means that the conductive layer has fewer defects and high uniformity, it is believed that not only the electrical properties of the conductive layer are excellent, but also the mechanical properties are excellent. The conductive particles of the present invention can be suitably manufactured using the above-mentioned manufacturing method of the present invention.
[0067] The withstand current value of the present invention is a value obtained by measuring the withstand current value of an average conductive particle at a compression rate of 30% using a conductive particle electrical property measuring device (hereinafter sometimes referred to as a VI device). When the electrodes are connected under pressure, it is necessary to compress and deform the conductive particles to increase the contact area with the electrodes. Therefore, it is important that the withstand current value in the compressed state is large. The VI device can be any device that can measure the voltage-current characteristics and / or current capacity while maintaining a constant compression rate of the conductive particles. For example, the device described in Japanese Patent Gazette No. 10-221388 can be used.
[0068] The withstand current value in the present invention is a value measured for each conductive particle. The withstand current value is preferably measured under conditions closer to those during installation, and the compression rate of the conductive particles to be measured is preferably 30%.
[0069] When the conductive particles of the present invention are used as conductive fillers of a conductive adhesive as described later, the surface of the conductive particles may be further covered with an insulating resin in order to prevent short circuits between the conductive particles. The insulating resin is covered in a manner that the surface of the conductive particles is not exposed as much as possible when no pressure is applied, and in a manner that at least protrusions are exposed on the surface of the conductive particles due to damage caused by heat and pressure applied when two electrodes are bonded using a conductive adhesive. The thickness of the insulating resin may be about 0.1 to 0.5 μm. The insulating resin may cover the entire surface of the conductive particles, or may cover only a portion of the surface of the conductive particles.
[0070] As the insulating resin, resins known in the art can be widely used. If an example is given, resins composed of organic polymers such as phenolic resin, urea resin, melamine resin, allyl resin, furan resin, polyester resin, epoxy resin, silicone resin, polyamide-imide resin, polyimide resin, polyurethane resin, fluororesin, polyolefin resin (e.g., polyethylene, polypropylene, polybutene), poly(meth)acrylic acid alkyl ester resin, poly(meth)acrylic acid resin, polystyrene resin, acrylonitrile-styrene-butadiene resin, vinyl resin, polyamide resin, polycarbonate resin, polyacetal resin, ionomer resin, polyethersulfone resin, polyphenylene oxide resin, polysulfone resin, polyvinylidene fluoride resin, ethyl cellulose resin, and cellulose acetate resin can be cited.
[0071] Methods for forming an insulating coating layer on the surface of conductive particles include chemical methods such as coagulation, interfacial polymerization, in situ polymerization, and liquid solidification coating; physical and mechanical methods such as spray drying, air suspension coating, vacuum evaporation coating, dry mixing, mixing, electrostatic fusion, melt dispersion cooling, and inorganic encapsulation; and physical and chemical methods such as interfacial precipitation.
[0072] The organic polymer constituting the above-mentioned insulating resin is non-conductive, and a compound containing an ionic group may be contained as a monomer component in the structure of the polymer. The compound containing an ionic group may be a crosslinking monomer or a non-crosslinking monomer. In other words, it is preferred that at least one of the crosslinking monomer and the non-crosslinking monomer use a compound having an ionic group to form an organic polymer. "Monomer component" refers to a structure derived from a monomer in an organic polymer, and is a component derived from a monomer. By subjecting a monomer to polymerization, an organic polymer containing the monomer component as a constituent unit can be formed.
[0073] The ionic group is preferably present at the interface of the organic polymer constituting the insulating resin. In addition, the ionic group is preferably chemically bonded to the monomer component constituting the organic polymer. When an insulating resin containing an organic polymer having an ionic group is formed on the surface of the conductive particles, it is possible to determine whether the ionic group is present at the interface of the organic polymer by observing whether the insulating resin is attached to the surface of the conductive particles using a scanning electron microscope.
[0074] Examples of the ionic group include onium functional groups such as phosphonium, ammonium, and sulfonium. Among these, from the viewpoint of improving the adhesion between the conductive particles and the insulating resin and forming conductive particles having both insulating properties and conduction reliability at a high level, an ammonium group or a phosphonium group is preferred, and a phosphonium group is more preferred.
[0075] Preferred examples of the onium functional group include groups represented by the following general formula (1).
[0076]
[0077] (In the formula, X is a phosphorus atom, a nitrogen atom or a sulfur atom, and R may be the same or different and is a hydrogen atom, a linear, branched or cyclic alkyl group, or an aryl group. n is 1 when X is a nitrogen atom or a phosphorus atom, and is 0 when X is a sulfur atom. * is a valence bond.)
[0078] As the counter ion corresponding to the ionic group, for example, a halide ion can be mentioned. Examples of halide ions include Cl - 、F - Br - ,I - .
[0079] In formula (1), examples of the straight-chain alkyl group represented by R include straight-chain alkyl groups having 1 to 20 carbon atoms, specifically methyl, ethyl, n-propyl, n-butyl, n-pentyl, n-hexyl, n-heptyl, n-octyl, n-nonyl, n-decyl, n-undecyl, n-dodecyl, n-tridecyl, n-tetradecyl, n-pentadecyl, n-hexadecyl, n-heptadecyl, n-octadecyl, n-nonadecyl, and n-eicosyl groups.
[0080] In formula (1), examples of the branched alkyl group represented by R include branched alkyl groups having 3 to 8 carbon atoms, specifically isopropyl, isobutyl, sec-butyl, tert-butyl, isopentyl, sec-pentyl, tert-pentyl, isohexyl, sec-hexyl, tert-hexyl, ethylhexyl and the like.
[0081] In the formula (1), examples of the cyclic alkyl group represented by R include cycloalkyl groups such as cyclopropyl, cyclobutyl, cyclopentyl, cyclohexyl, cycloheptyl, cyclooctyl and cyclooctadecyl.
[0082] In the formula (1), examples of the aryl group represented by R include phenyl, benzyl, tolyl, and o-xylyl.
[0083] In the general formula (1), R is preferably an alkyl group having 1 to 12 carbon atoms, more preferably an alkyl group having 1 to 10 carbon atoms, and further preferably an alkyl group having 1 to 8 carbon atoms. In the general formula (1), R is further preferably a straight-chain alkyl group. By forming the onium functional group in such a structure, the adhesion between the insulating resin and the conductive particles can be improved, the insulation can be ensured, and the conduction reliability during thermal compression bonding can be further improved.
[0084] From the viewpoint of facilitating the acquisition of monomers and synthetic polymers and improving the production efficiency of the insulating resin, the organic polymer having an ionic group constituting the insulating resin preferably has a structural unit represented by the following general formula (2) or (3).
[0085]
[0086] (wherein, X, R and n have the same meanings as in the above general formula (1). m is an integer from 0 to 5. - represents a monovalent anion.)
[0087]
[0088] (wherein, X, R and n have the same meanings as in the above general formula (1). - Represents a monovalent anion. m 1 is an integer from 1 to 5. R5 is a hydrogen atom or a methyl group.
[0089] As examples of R in formula (2) and formula (3), the description of the functional group of R in the above general formula (1) can be appropriately adopted. The ionic group may be bonded to any of the para, ortho, and meta positions relative to the CH group of the benzene ring of formula (2), preferably to the para position. In formula (2) and formula (3), the monovalent An - , preferably halide ions. Examples of halide ions include Cl - 、F - Br - ,I - .
[0090] In the general formula (2), m is preferably an integer of 0 or more and 2 or less, more preferably 0 or 1, and particularly preferably 1. In the general formula (3), m 1 It is preferably 1 or more and 3 or less, more preferably 1 or 2, and most preferably 2.
[0091] The organic polymer having an ionic group preferably contains a monomer component having an onium functional group and an ethylenically unsaturated bond. From the viewpoint of easily obtaining monomers and synthesizing polymers and improving the manufacturing efficiency of insulating resins, the organic polymer having an ionic group preferably contains a non-crosslinking monomer component.
[0092] Examples of the non-crosslinking monomer having an onium functional group and an ethylenically unsaturated bond include: an ammonium group-containing monomer such as N,N-dimethylaminoethyl methacrylate, N,N-dimethylaminopropyl acrylamide, and N,N,N-trimethyl-N-2-methacryloyloxyethyl ammonium chloride; a monomer having a sulfonium group such as methacrylate phenyldimethylsulfonium methylsulfate; 4-(vinylbenzyl)triethylphosphonium chloride, 4-(vinylbenzyl)trimethylphosphonium chloride; , 4-(vinylbenzyl)tributylphosphonium chloride, 4-(vinylbenzyl)trioctylphosphonium chloride, 4-(vinylbenzyl)triphenylphosphonium chloride, 2-(methacryloyloxyethyl)trimethylphosphonium chloride, 2-(methacryloyloxyethyl)triethylphosphonium chloride, 2-(methacryloyloxyethyl)tributylphosphonium chloride, 2-(methacryloyloxyethyl)trioctylphosphonium chloride, 2-(methacryloyloxyethyl)triphenylphosphonium chloride and other monomers having a phosphonium group. The organic polymer having an ionic group may contain two or more non-crosslinking monomer components.
[0093] In the organic polymer constituting the insulating resin, the ionic group may be bonded to all monomer components, or the ionic group may be bonded to a portion of all constituent units of the organic polymer. In the case where the ionic group is bonded to a portion of all constituent units of the organic polymer, the proportion of the monomer component to which the ionic group is bonded is preferably 0.01 mol% to 99 mol%, more preferably 0.02 mol% to 95 mol%. Among them, the number of monomer components in the organic polymer counts the structure from one ethylenically unsaturated bond as one monomer constituent unit. In the case where both the crosslinking monomer and the non-crosslinking monomer contain ionic groups, the proportion of the monomer component is its total amount.
[0094] Examples of the coating with the insulating resin include a coating in which a plurality of insulating fine particles are arranged in layers or an insulating continuous coating.
[0095] In the case where the insulating resin is composed of insulating particles, the insulating particles covered by the insulating particles are thermally pressed between the electrodes, and the insulating particles are melted, deformed, peeled off, or moved on the surface of the conductive particles, thereby exposing the metal surface of the conductive particles in the thermally pressed portion, thereby achieving conduction between the electrodes and obtaining connectivity. On the other hand, the surface portion of the conductive particles facing the direction other than the thermally pressed direction roughly maintains the state where the insulating particles cover the surface of the conductive particles, so that conduction in the direction other than the thermally pressed direction can be prevented.
[0096] The insulating particles contain the above-mentioned ionic groups on their surfaces, so that they can be easily attached to the conductive particles, thereby making it possible to make the proportion of the conductive particle surface covered by the insulating particles sufficient, and effectively prevent the insulating particles from being peeled off from the conductive particles. Therefore, the insulating particles can easily exert the effect of preventing short circuits in a direction different from that between the opposing electrodes, and it can be expected that the insulation in this direction will be improved.
[0097] The shape of the insulating particles is not particularly limited, and may be spherical or may be a shape other than spherical. Shapes other than spherical include, for example, fibrous, hollow, plate-like or needle-like. The insulating particles may also be particles having a plurality of protrusions on the surface thereof, or may be amorphous particles. Spherical insulating particles are preferred from the perspective of adhesion to the conductive particles and ease of synthesis.
[0098] The average particle size (D) of the insulating fine particles is preferably 10 nm to 3,000 nm, more preferably 15 nm to 2,000 nm. When the average particle size of the insulating fine particles is within the above range, the obtained covered particles will not short-circuit in a direction different from that between the opposing electrodes, and it is easy to ensure conduction between the opposing electrodes. In the present invention, the average particle size of the insulating fine particles is a value measured by observation using a scanning electron microscope, and is specifically measured by the method described in the examples described below.
[0099] The particle size distribution of the insulating fine particles measured by the above method has a width. Generally, the width of the particle size distribution of a powder is represented by the coefficient of variation (hereinafter also referred to as "CV") shown in the following calculation formula (1).
[0100] CV (%) = (standard deviation / average particle size) × 100 (1)
[0101] When the CV is large, the width of the particle size distribution is wide, while when the CV is small, the particle size distribution is narrow. The coated particles of this embodiment preferably use insulating particles with a CV of preferably 0.1% to 20%, more preferably 0.5% to 15%, and most preferably 1% to 10%. When the CV is within this range, there is an advantage that the thickness of the coating layer using the insulating particles can be made uniform.
[0102] In addition, as an insulating resin, a continuous coating composed of a polymer and having ionic groups can also be used to replace the above-mentioned insulating resin composed of insulating particles. In the case where the insulating resin is a continuous coating having ionic groups, by hot pressing the conductive particles between electrodes, the continuous coating melts, deforms or peels off, thereby exposing the metal surface of the conductive particles, thereby enabling conduction between the electrodes and obtaining connectivity. In particular, by hot pressing the conductive particles between electrodes, the continuous coating is destroyed in most cases, thereby exposing the metal surface. On the other hand, in the surface portion of the conductive particles facing a direction different from the hot pressing direction, the state of the continuous coating covering the conductive particles is roughly maintained, thereby preventing conduction in directions other than the hot pressing direction. The continuous coating also preferably has ionic groups on the surface.
[0103] The thickness of the continuous coating is preferably 10 nm or more from the perspective of improving insulation in a direction different from the opposing electrodes, and is preferably 3,000 nm or less from the perspective of ease of conduction between the opposing electrodes. From this point of view, the thickness of the continuous coating is preferably 10 nm or more and 3,000 nm or less, and more preferably 15 nm or more and 2,000 nm or less.
[0104] Similar to the insulating particles, in the continuous film, the ionic group preferably becomes part of the chemical structure of the substance in the form of a part of the substance constituting the continuous film. In the continuous film, it is preferred that at least one structure of the constituent unit of the polymer constituting the continuous film contains the ionic group. The ionic group is preferably chemically bonded to the polymer constituting the continuous film, and more preferably bonded to the side chain of the polymer.
[0105] In the case where the insulating resin is a continuous coating, it is preferably a continuous coating obtained by heating the insulating particles after covering the conductive particles with insulating particles having ionic groups on their surfaces. Alternatively, it is preferably a continuous coating obtained by dissolving the insulating particles with an organic solvent. As described above, the insulating particles having ionic groups are easy to adhere to the conductive particles, so that the proportion of the conductive particle surface covered by the insulating particles becomes sufficient, and it is easy to prevent the insulating particles from peeling off the conductive particles. Therefore, the continuous coating obtained by heating or dissolving the insulating particles covering the conductive particles can be made into a product with uniform thickness and a high coverage ratio of the conductive particle surface.
[0106] Furthermore, the conductive particles of the present invention may be treated with a surface treatment agent in order to improve affinity with the insulating resin and improve adhesion.
[0107] Examples of the surface treatment agent include benzotriazole compounds, titanium compounds, higher fatty acids or derivatives thereof, phosphoric acid esters, and phosphites, etc. These may be used alone or in combination of two or more as required.
[0108] The surface treatment agent may or may not chemically bond to the metal on the surface of the conductive particles. The surface treatment agent only needs to be present on the surface of the conductive particles, and in this case, it may be present on the entire surface of the conductive particles or only on a portion of the surface.
[0109] Examples of the triazole compound include compounds having a nitrogen-containing heterocyclic structure containing three nitrogen atoms in a five-membered ring.
[0110] As triazole compounds, in addition to compounds having a triazole monocyclic structure not condensed with other rings, compounds having a ring structure formed by condensing a triazole ring with other rings can be listed. As other rings, benzene rings and naphthalene rings can be listed.
[0111] Among them, compounds having a ring structure in which a triazole ring and another ring are condensed are preferred from the viewpoint of excellent adhesion to the insulating resin, and benzotriazole compounds which are compounds having a structure in which a triazole ring and a benzene ring are condensed are particularly preferred.
[0112] Examples of the benzotriazole-based compound include compounds represented by the following general formula (I).
[0113]
[0114] (Where R 11 is a negative charge, a hydrogen atom, an alkali metal, an alkyl group, an amino group, a formyl group, a hydroxyl group, an alkoxy group, a sulfonic acid group or a silyl group which may be substituted, R 12 , R 13 , R 14 and R 15 are independently a hydrogen atom, a halogen atom, an alkyl group which may be substituted, a carboxyl group, a hydroxyl group or a nitro group.)
[0115] As R in formula (I) 11 The alkali metals shown include lithium, sodium, potassium, etc. 11 The alkali metal shown is an alkali metal cation. In formula (I), R 11 In the case of alkali metals, R 11 The bond with the nitrogen atom may be an ionic bond.
[0116] As R in formula (I) 11 , R 12 , R 13 , R 14 and R 15 The alkyl group shown in the formula (a) may be an alkyl group having 1 to 20 carbon atoms, and particularly preferably an alkyl group having 1 to 12 carbon atoms. The alkyl group may be substituted, and examples of the substituent include an amino group, an alkoxy group, a carboxyl group, a hydroxyl group, an aldehyde group, a nitro group, a sulfonic acid group, a quaternary ammonium group, a sulfonium group, a sulfonyl group, a phosphonium group, a cyano group, a fluoroalkyl group, a mercapto group, and a halogen atom.
[0117] As R 11 The alkoxy group shown is preferably an alkoxy group having 1 to 12 carbon atoms.
[0118] In addition, as R 12 , R 13 , R 14 and R 15 The number of carbon atoms of the alkoxy group of the alkyl group represented by is preferably 1 to 12. 12 , R 13 , R 14 and R 15 Examples of the halogen atom include a fluorine atom, a chlorine atom, a bromine atom, and an iodine atom.
[0119] Specific examples of triazole compounds include compounds having a triazole monocyclic structure, such as 1,2,3-triazole, 1,2,4-triazole, 3-amino-1H-1,2,4-triazole, 5-mercapto-1H-1,2,3-triazole sodium, 4-amino-3-hydrazino-5-mercapto-1,2,4-triazole, and 3-amino-5-mercapto-1,2,4-triazole. Examples include benzotriazole having a ring structure in which a triazole ring is condensed with another ring, 1-methyl-1H-benzotriazole, 4-methyl-1H-benzotriazole, 5-methyl-1H-benzotriazole, 4- Carboxyl-1H-benzotriazole, 5-carboxyl-1H-benzotriazole, 5-ethyl-1H-benzotriazole, 5-propyl-1H-benzotriazole, 5,6-dimethyl-1H-benzotriazole, 1-aminobenzotriazole, 5-nitrobenzotriazole, 5-chlorobenzotriazole, 4,5,6,7-tetrabromobenzotriazole, 1-hydroxybenzotriazole, 1-(methoxymethyl)-1H-benzotriazole, 1H-benzotriazole-1-methanol, 1H-benzotriazole-1-carboxaldehyde, 1-(chloromethyl)-1H-benzotriazole, 1-hydroxy-6-(trifluoromethyl)benzotriazole, butyl benzotriazole, 4-carboxy-1H-benzotriazole butyl ester, 4-carboxy-1H-benzotriazole octyl ester, 1-[N,N-bis(2-ethylhexyl)aminomethyl]methylbenzotriazole, 2,2'-[[(methyl-1H-benzotriazol-1-yl)methyl]imino]bisethanol, tetrabutylphosphonium benzotriazole salt, 1H-benzotriazol-1-yloxytris(dimethylamino)phosphonium hexafluorophosphate, 1H-benzotriazol-1-yloxytripyrrolidinophosphonium hexafluorophosphate, 1-(formamidomethyl)-1H-benzotriazole, 1-[bis(dimethylamino)methylene]-1H-benzotriazolium-3-oxide hexafluorophosphate fluorophosphate, 1-[bis(dimethylamino)methylene]-1H-benzotriazolium-3-oxide tetrafluoroborate, (6-chloro-1H-benzotriazol-1-yloxy)tripyrrolidinylphosphonium hexafluorophosphate, O-(benzotriazol-1-yl)-N,N,N',N'-bis(tetramethylene)uronium hexafluorophosphate, O-(6-chlorobenzotriazol-1-yl)-N,N,N',N'-tetramethyluronium tetrafluoroborate, O-(6-chlorobenzotriazol-1-yl)-N,N,N',N'-tetramethyluronium hexafluorophosphate,N'-bis(pentamethylene)uronium hexafluorophosphate, 1-(trimethylsilyl)-1H-benzotriazole, 1-[2-(trimethylsilyl)ethoxycarbonyloxy]benzotriazole, 1-(trifluoromethanesulfonyl)-1H-benzotriazole, (trifluoroacetyl)benzotriazole, tri(1H-benzotriazol-1-yl)methane, 9-(1H-benzotriazol-1-ylmethyl)-9H-carbazole, [(1H-benzotriazol-1-yl)methyl]triphenylphosphonium chloride, 1-(isocyanatomethyl)-1H-benzotriazole, 1-[(9H-fluoren-9-ylmethoxy)carbonyloxy]benzotriazole, 1,2,3-benzotriazole sodium salt, naphthotriazole, etc.
[0120] As the above-mentioned titanium compound, for example, when it is present on the surface of conductive particles, a compound having a structure represented by general formula (II) is particularly preferred from the perspective of easily obtaining affinity between the insulating resin and the conductive particles, being easily dispersed in a solvent, and being able to uniformly treat the surface of the conductive particles.
[0121]
[0122] (R 21 is a divalent or trivalent group, R 22 is an aliphatic hydrocarbon group having 2 to 30 carbon atoms, an aryl group having 6 to 22 carbon atoms, or an arylalkyl group having 7 to 23 carbon atoms, p and r are each an integer of 1 to 3 and satisfy p+r=4, q is an integer of 1 or 2, and in R 21 When it is a divalent group, q is 1. 21 When q is 2, multiple R 22 They can be the same or different. * indicates a bond. )
[0123] As R 22 Examples of aliphatic hydrocarbon groups having 4 to 28 carbon atoms include methyl, ethyl, propyl, butyl, pentyl, hexyl, heptyl, octyl, nonyl, decyl, dodecyl, tridecyl, tetradecyl, pentadecyl, hexadecyl, heptadecyl, octadecyl, nonadecyl, eicosyl, heneicosyl, and docosyl. Examples of unsaturated aliphatic hydrocarbon groups include alkenyl groups including dodecenyl, tridecenyl, tetradecenyl, pentadecenyl, hexadecenyl, heptadecenyl, nonadecenyl, icosenyl, eicosenyl, heneicosyl, and docosyl.
[0124] Examples of the aryl group having 6 to 22 carbon atoms include phenyl, tolyl, naphthyl, and anthracenyl.
[0125] Examples of the arylalkyl group having 7 to 23 carbon atoms include benzyl, phenethyl, and naphthylmethyl.
[0126] As the hydrophobic group, a linear or branched aliphatic hydrocarbon group is particularly preferred, and a linear aliphatic hydrocarbon group is particularly preferred.
[0127] From the viewpoint of improving the affinity between the insulating resin and the conductive particles, the aliphatic hydrocarbon group as the hydrophobic group is particularly preferably a group having 4 to 28 carbon atoms, and most preferably a group having 6 to 24 carbon atoms.
[0128] As R 21 Examples of the divalent group shown include -O-, -COO-, -OCO-, and -OSO2-. 21 Examples of the trivalent group shown include -P(OH)(O-)2, -OPO(OH)-OPO(O-)2 and the like.
[0129] In the general formula (II), * is a bond, which may be bonded to the metal coating of the conductive particles or to other groups, etc. Examples of other groups include hydrocarbon groups, specifically alkyl groups having 1 to 12 carbon atoms.
[0130] As the titanium compound having a structure represented by the general formula (II), from the viewpoint of easy availability and handling without impairing the conductive properties of the conductive particles, a titanium compound having R in the general formula (II) is preferably 21 A compound having a structure of a divalent group. R in the general formula (II) 21 The structure which is a divalent group is represented by the following general formula (III).
[0131]
[0132] (R 21 is a group selected from -O-, -COO-, -OCO-, -OSO2-, p, r and R 22 The meaning is the same as that of general formula (II).
[0133] In the general formulae (II) and (III), r is preferably 2 or 3, and most preferably 3, from the viewpoint of improving the adhesion between the insulating resin and the conductive layer.
[0134] Specific examples of the titanate coupling agent used in the present invention include isopropyl triisostearoyl titanate, isopropyl tri(dodecylbenzenesulfonyl) titanate, isopropyl tri(dioctyl pyrophosphate) titanate, tetraisopropyl(dioctyl phosphite) titanate, tetraisopropyl bis(dioctyl phosphite) titanate, tetraoctyl bis(ditridecyl phosphite) titanate, tetra(2,2-diallyloxymethyl-1-butyl)bis(ditridecyl) phosphite titanate, bis(dioctyl pyrophosphate)oxyacetate titanate, and bis(dioctyl pyrophosphate)ethylene titanate. One or more of these may be used.
[0135] In addition, these titanate-based coupling agents are commercially available from, for example, Ajinomoto Fine-Techno Co., Ltd.
[0136] As the higher fatty acid, preferably a saturated or unsaturated straight chain or branched mono or polycarboxylic acid, more preferably a saturated or unsaturated straight chain or branched monocarboxylic acid, further preferably a saturated or unsaturated straight chain monocarboxylic acid. The carbon number of the fatty acid is preferably 7 or more. In addition, the derivative refers to the salt or amide of the above-mentioned fatty acid.
[0137] Regarding the higher fatty acids or their derivatives used in the present invention, the number of carbon atoms of the higher fatty acids is preferably 7 to 23, and more preferably 10 to 20. As such higher fatty acids or their derivatives, for example, saturated fatty acids such as capric acid, lauric acid, myristic acid, palmitic acid, and stearic acid, unsaturated fatty acids such as oleic acid, linoleic acid, linolenic acid, and arachidonic acid, or their metal salts or amides, etc. As metal salts of higher fatty acids, alkali metals, alkaline earth metals, transition metals such as Zr, Cr, Mn, Fe, Co, Ni, Cu, and Ag, and salts of other metals other than transition metals such as Al and Zn can be listed, preferably polyvalent metal salts of Al, Zn, W, and V. The higher fatty acid metal salt can be one, two, three, four, etc. according to the valence of the metal. The higher fatty acid metal salt can also be any combination of them.
[0138] As the phosphoric acid ester and the phosphorous acid ester, an ester having an alkyl group having 6 to 22 carbon atoms is preferably used.
[0139] Examples of the phosphoric acid ester include hexyl phosphate, heptyl phosphate, monooctyl phosphate, monononyl phosphate, monodecyl phosphate, monoundecyl phosphate, monododecyl phosphate, monotridecyl phosphate, monotetradecyl phosphate, and monopentadecyl phosphate.
[0140] Examples of the phosphite include hexyl phosphite, heptyl phosphite, monooctyl phosphite, monononyl phosphite, monodecyl phosphite, monoundecyl phosphite, monododecyl phosphite, monotridecyl phosphite, monotetradecyl phosphite, and monopentadecyl phosphite.
[0141] In the present invention, from the perspective of excellent affinity with the insulating resin and high effect of improving the coverage of the insulating resin, the surface treatment agent is preferably a triazole compound or a titanium compound, and particularly preferably benzotriazole, 4-carboxybenzotriazole, isopropyl triisostearyl titanate, and tetraisopropyl (dioctyl phosphite) titanate.
[0142] Regarding the method of treating the conductive particles with a surface treatment agent, the conductive particles are dispersed in a solution of the surface treatment agent and then filtered. Before the treatment with the surface treatment agent, the conductive particles may be treated with other treatment agents or may not be treated.
[0143] The concentration of the surface treatment agent in the solution of the surface treatment agent for dispersing the conductive particles (the solution containing the conductive particles) can be 0.01 mass % or more and 10.0 mass % or less. In addition, the solvent in the solution of the surface treatment agent can be water, methanol, ethanol, 1-propanol, 2-propanol, 1-butanol, 2-butanol, isobutanol, isoamyl alcohol, cyclohexanol and other alcohols, acetone, methyl isobutyl ketone, methyl ethyl ketone, methyl-n-butyl ketone and other ketones, methyl acetate, ethyl acetate and other esters, diethyl ether, ethylene glycol monoethyl ether and other ethers, n-hexane, cyclohexanone, toluene, 1,4-dioxane, N,N-dimethylformamide, tetrahydrofuran and the like. The conductive particles after the surface treatment after dispersion and filtration are preferably dispersed again in a solvent to remove excess surface treatment agent.
[0144] The surface treatment of the conductive particles with the surface treatment agent can be carried out by mixing the conductive particles, the surface treatment agent and the solvent at room temperature. Alternatively, the conductive particles and the surface treatment agent can be mixed in a solvent and then heated to promote the reaction. The heating temperature can be, for example, 30° C. to 50° C.
[0145] The conductive particles of the present invention have low connection resistance and excellent connection reliability, so they are suitable for use as anisotropic conductive films (ACF) or heat seal contactors (HSC), and conductive materials for connecting the electrodes of liquid crystal display panels to the circuit substrates of driving LSI chips. As the conductive material, the case of directly using the conductive particles of the present invention or the material obtained by dispersing the conductive particles of the present invention in a binder resin can be cited. Other forms of the conductive material are not particularly limited, and in addition to the above-mentioned forms, for example, forms such as anisotropic conductive pastes, conductive adhesives, and anisotropic conductive inks can also be cited.
[0146] Examples of the binder resin include thermoplastic resins and thermosetting resins. Examples of the thermoplastic resins include acrylic resins, styrene resins, ethylene-vinyl acetate resins, and styrene-butadiene block copolymers; examples of the thermosetting resins include epoxy resins, phenolic resins, urea resins, polyester resins, polyurethane resins, and polyimide resins.
[0147] In addition to the conductive particles and binder resin of the present invention, the above-mentioned conductive materials can also be combined with tackifiers, reactive auxiliary agents, epoxy resin curing agents, metal oxides, photoinitiators, sensitizers, curing agents, vulcanizers, anti-degradation agents, heat-resistant additives, thermal conductivity enhancers, softeners, colorants, various coupling agents or metal passivators, etc. as needed.
[0148] In the above-mentioned conductive material, the amount of conductive particles used can be appropriately determined according to the application. From the viewpoint of easily obtaining electrical conduction without the conductive particles contacting each other, for example, it is preferably from 0.01 to 50 parts by mass, and particularly preferably from 0.03 to 40 parts by mass, relative to 100 parts by mass of the conductive material.
[0149] Among the above-mentioned forms of conductive materials, the conductive particles of the present invention are particularly suitable for use as a conductive filler in a conductive adhesive.
[0150] The above-mentioned conductive adhesive is preferably used as an anisotropic conductive adhesive that is arranged between two substrates formed with a conductive substrate, and the above-mentioned conductive substrates are bonded and conducted by heating and pressing. The anisotropic conductive adhesive comprises the conductive particles of the present invention and an adhesive resin. As an adhesive resin, as long as it is an insulating resin that can be used as an adhesive resin, it can be used without particular restrictions. Both thermoplastic resins and thermosetting resins are possible, and resins that exhibit bonding properties by heating are preferred. Such adhesive resins include, for example, thermoplastic, thermosetting, and ultraviolet curing types. There are also so-called semi-thermosetting types that exhibit intermediate properties between thermoplastic and thermosetting types, and composite types of thermosetting and ultraviolet curing types. These adhesive resins can be appropriately selected according to the surface characteristics and usage form of the circuit substrate, etc., which are the objects to be bonded. From the perspective of excellent material strength after bonding, adhesive resins composed of thermosetting resins are particularly preferred.
[0151] As the adhesive resin, specifically, materials prepared with a resin selected from ethylene-vinyl acetate copolymer, carboxyl-modified ethylene-vinyl acetate copolymer, ethylene-isobutyl acrylate copolymer, polyamide, polyimide, polyester, polyvinyl ether, polyvinyl butyral, polyurethane, SBS block copolymer, carboxyl-modified SBS copolymer, SIS copolymer, SEBS copolymer, maleic acid-modified SEBS copolymer, polybutadiene rubber, chloroprene rubber, carboxyl-modified chloroprene rubber, styrene-butadiene rubber, isobutylene-isoprene copolymer, acrylonitrile-butadiene rubber (hereinafter referred to as NBR), carboxyl-modified NBR, amine-modified NBR, epoxy resin, epoxy ester resin, acrylic resin, phenolic resin or silicone resin as the main agent can be cited. Among these, as thermoplastic resins, styrene-butadiene rubber and SEBS are preferred because of their excellent reprocessability. As a thermosetting resin, epoxy resin is preferred. Among these, epoxy resin is most preferable because of its advantages of high adhesive strength, excellent heat resistance and electrical insulation, low melt viscosity, and ability to connect at low pressure.
[0152] As the above-mentioned epoxy resin, as long as it is a polycyclic epoxy resin having more than two epoxy groups in one molecule, a commonly used epoxy resin can be used. As specific examples, phenol novolac resins such as cresol novolac, polyphenols such as bisphenol A, bisphenol F, bisphenol AD, resorcinol, dihydroxy diphenyl ether, polyols such as ethylene glycol, neopentyl glycol, glycerine, trimethylolpropane, polypropylene glycol, polyamino compounds such as ethylenediamine, triethylenetetramine, aniline, adipic acid, phthalic acid, isophthalic acid, etc., polycarboxyl compounds such as glycidyl epoxy resins obtained by reacting with epichlorohydrin or 2-methyl epichlorohydrin can be illustrated. Aliphatic and alicyclic epoxy resins such as epoxidized dicyclopentadiene and diepoxidized dipolybutadiene can also be cited. These can be used alone or in combination of two or more.
[0153] In addition, as the above-mentioned various adhesive resins, from the viewpoint of preventing ion migration, it is preferable to use a high-purity product in which impurity ions (Na, Cl, etc.) and hydrolyzable chlorine, etc., are reduced.
[0154] The amount of the conductive particles in the anisotropic conductive adhesive is usually 0.1 to 30 parts by mass, preferably 0.5 to 25 parts by mass, and more preferably 1 to 20 parts by mass, relative to 100 parts by mass of the adhesive resin component. When the amount of the conductive particles is within this range, the connection resistance and melt viscosity can be suppressed, the connection reliability can be improved, and the anisotropy of the connection can be fully ensured.
[0155] In the above-mentioned anisotropic conductive adhesive, in addition to the above-mentioned conductive particles and adhesive resin, additives known in the technical field may also be added. The amount thereof may also be within the range known in the technical field. As other additives, for example, tackifiers, reactive auxiliary agents, epoxy resin curing agents, metal oxides, photoinitiators, sensitizers, curing agents, vulcanizing agents, anti-degradation agents, heat-resistant additives, thermal conductivity enhancers, softeners, colorants, various coupling agents or metal passivators may be exemplified.
[0156] As tackifiers, for example, rosin, rosin derivatives, terpene resins, terpene phenolic resins, petroleum resins, coumarone-indene resins, styrene resins, isoprene resins, alkylphenolic resins, xylene resins, etc. can be cited. As reactive auxiliary agents, i.e., crosslinking agents, for example, polyols, isocyanates, melamine resins, urea resins, urotropines (Utropins), amines, acid anhydrides, peroxides, etc. can be cited. As epoxy resin curing agents, as long as they are substances with more than two active hydrogens in one molecule, they can be used without particular restrictions. As specific examples, for example, polyamino compounds such as diethylenetriamine, triethylenetetramine, metaphenylenediamine, dicyandiamide, and polyamideamines can be cited; organic acid anhydrides such as phthalic anhydride, methylnadic anhydride, hexahydrophthalic anhydride, and pyromellitic anhydride; phenolic novolac resins such as phenol novolac and cresol novolac, etc. These can be used alone or in combination of two or more. As required, a latent curing agent may also be used. Examples of the latent curing agent that can be used include imidazoles, hydrazides, boron trifluoride-amine complexes, sulfonium salts, amine imides, salts of polyamines, dicyandiamide, and their modified products. These may be used alone or in the form of a mixture of two or more.
[0157] The above-mentioned anisotropic conductive adhesive can be manufactured using a manufacturing device commonly used in the technical field. For example, conductive particles and adhesive resin, as well as a curing agent and various additives as required, are mixed in an organic solvent when the adhesive resin is a thermosetting resin, and when the adhesive resin is a thermoplastic resin, melt-kneading is performed at a temperature above the softening point of the adhesive resin, specifically preferably about 50 to 130° C., more preferably about 60 to 110° C., thereby manufacturing. The anisotropic conductive adhesive thus obtained can be applied or used after being formed into a film.
[0158] By connecting two circuit substrates to each other using the conductive particles of the present invention or a conductive material containing the conductive particles, a connection structure can be obtained. Examples of the connection structure include a connection structure between a flexible printed substrate and a glass substrate, a connection structure between a semiconductor chip and a flexible printed substrate, and a connection structure between a semiconductor chip and a glass substrate.
[0159] Example
[0160] The present invention will be further described below using examples, but the scope of the present invention is not limited to these examples.
[0161] The properties in the examples were measured by the following methods.
[0162] (1) Average particle size
[0163] 200 particles were randomly selected from a scanning electron microscope (SEM) photograph of the measurement object, and the particle diameters were measured at a magnification of 10,000 times, and the arithmetic mean value was taken as the average particle diameter.
[0164] (2) Thickness of the conductive layer
[0165] The conductive particles were cut in half, and the cross section of the cut was observed using a scanning electron microscope (SEM) for measurement.
[0166] (3) Withstand current value
[0167] The current value (mA) flowing when the compression rate of the conductive particles was 30% was measured using a conductive fine particle electrical property device (VI device, a device prepared by referring to the device described in Japanese Patent Application Laid-Open No. 10-221388).
[0168] [Example 1]
[0169] (1) Pretreatment
[0170] Spherical styrene-acrylate-silica composite resin particles with an average particle size of 3.0 μm were used as core particles. 9 g of the particles were added to 200 mL of a conditioning agent aqueous solution ("Cleaner Conditioner 231" manufactured by Rohm and Haas Electronic Materials) while stirring. The concentration of the conditioning agent aqueous solution was 40 mL / L. Then, ultrasonic waves were applied at a liquid temperature of 60°C and stirred for 30 minutes to perform surface modification and dispersion treatment of the core particles. After filtering the aqueous solution, the core particles that had been re-pulped and washed were made into a 200 mL slurry. 0.1 g of stannous chloride was added to the slurry. Stirring was performed at room temperature for 5 minutes to perform a sensitization treatment to adsorb tin ions on the surface of the core particles. Then, the aqueous solution was filtered, and the core particles that had been re-pulped and washed were made into a 200 mL slurry and maintained at 60°C. 1.5 mL of a 0.11 mol / L palladium chloride aqueous solution was added to the slurry. The core particles were stirred at 60°C for 5 minutes to activate the surface of the core particles to capture palladium ions. The aqueous solution was then filtered, and the core particles were washed with hot water once to prepare a 100 mL slurry. 10 mL of a 0.5 g / L dimethylamine borane aqueous solution was added, and ultrasonic waves were applied and stirred for 2 minutes to obtain a slurry of the pre-treated core particles.
[0171] (2) Preparation of plating bath
[0172] 3 L of an electroless nickel-phosphorus plating bath formed of an aqueous solution containing 5 g / L of sodium tartrate, 2 g / L of nickel sulfate hexahydrate, 10 g / L of trisodium citrate, 0.1 g / L of sodium hypophosphite, and 2 g / L of polyethylene glycol was prepared and heated to 70°C.
[0173] (3) Electroless plating
[0174] The slurry of the core particles that had undergone the above pretreatment was added to the electroless plating bath and stirred for 5 minutes, and then it was confirmed that the bubbling of hydrogen gas had stopped.
[0175] To the slurry, 420 mL of a 224 g / L nickel sulfate aqueous solution and 420 mL of a mixed aqueous solution containing 210 g / L sodium hypophosphite and 80 g / L sodium hydroxide were continuously added using a metering pump at a rate of 2.5 mL / min to start electroless plating.
[0176] After adding the entire amount of the nickel sulfate aqueous solution and the mixed aqueous solution of sodium hypophosphite and sodium hydroxide, the temperature was maintained at 70°C and stirring was continued for 5 minutes. Next, the liquid was filtered, and the filtrate was washed three times and then dried in a vacuum dryer at 110°C to obtain conductive particles with a nickel-phosphorus alloy coating. The obtained conductive particles had an average particle size of 3.22 μm, a conductive layer thickness of 110 nm, and protrusions.
[0177] (4) Vacuum heating treatment
[0178] The obtained conductive particles are placed in a square container to a thickness of 5 mm. They are placed in a vacuum heating furnace (KDF-75 manufactured by Denken Highdental) and heated from room temperature to 390°C at a heating rate of 5°C / min under a vacuum of 10 Pa, and then heat treated at this temperature for 2 hours. After the heat treatment, nitrogen is placed to atmospheric pressure, and then nitrogen is blown in, thereby cooling to room temperature at a cooling rate of 3°C / min to obtain heat-treated conductive particles. The average particle size of the conductive particles obtained is 3.22μm, the thickness of the conductive layer is 110nm, and it has protrusions. In addition, the results of measuring the withstand current value of the obtained conductive particles are shown in Table 1.
[0179] [Example 2]
[0180] The vacuum heat treatment (4) in Example 1 was carried out according to the following operation. The conductive particles obtained by the electroless plating treatment (3) in Example 1 were placed in a square container so as to have a thickness of 5 mm. They were placed in a heating furnace (KDF-75 manufactured by Denken Highdental Co., Ltd.) and heated from room temperature to 390°C at a heating rate of 5°C / min under a vacuum of 100 Pa, and then heated at this temperature for 2 hours. After the heat treatment, nitrogen was placed in the container to make it atmospheric pressure, and then nitrogen was blown in, thereby cooling to room temperature at a cooling rate of 3°C / min to obtain conductive particles that had been heat-treated. The average particle size of the conductive particles obtained was 3.22 μm, the thickness of the conductive layer was 110 nm, and it had protrusions. In addition, the withstand current value of the conductive particles obtained was measured and the results are shown in Table 1.
[0181] [Example 3]
[0182] The vacuum heat treatment (4) in Example 1 was carried out according to the following operation. The conductive particles obtained by the electroless plating treatment (3) in Example 1 were placed in a square container so as to have a thickness of 5 mm. They were placed in a heating furnace (KDF-75 manufactured by Denken Highdental Co., Ltd.) and heated from room temperature to 320°C at a heating rate of 5°C / min under a vacuum of 10 Pa, and then heat-treated at this temperature for 2 hours. After the heat treatment, nitrogen was placed in the container to make it atmospheric pressure, and then nitrogen was blown in, thereby cooling to room temperature at a cooling rate of 3°C / min to obtain conductive particles that had been heat-treated. The conductive particles obtained had an average particle size of 3.22 μm, a thickness of the conductive layer of 110 nm, and had protrusions. In addition, the withstand current value of the conductive particles obtained was measured and the results are shown in Table 1.
[0183] [Comparative Example 1]
[0184] The conductive particles obtained by the electroless plating treatment (3) of Example 1 were used as the conductive particles of Comparative Example 1. Table 1 shows the results of measuring the withstand current values of the conductive particles.
[0185] [Comparative Example 2]
[0186] The following operation is performed to replace the vacuum heat treatment (4) in Example 1. The conductive particles obtained by the electroless plating treatment (3) in Example 1 are placed in a square container so that they have a thickness of 5 mm. They are placed in a heating furnace (KDF-75 manufactured by Denken Highdental Co., Ltd.) and heat-treated at 260°C for 2 hours under normal pressure in a nitrogen atmosphere. After the heat treatment, the mixture is cooled to room temperature to obtain heat-treated conductive particles. The average particle size of the conductive particles obtained is 3.22 μm, the thickness of the conductive layer is 110 nm, and the conductive layer has protrusions. In addition, the withstand current value of the conductive particles obtained is measured and the results are shown in Table 1.
[0187] [Comparative Example 3]
[0188] The following operation is performed to replace the vacuum heat treatment (4) in Example 1. The conductive particles obtained by the electroless plating treatment (3) in Example 1 are placed in a square container to a thickness of 5 mm. They are placed in a heating furnace (KDF-75 manufactured by Denken Highdental) and heat-treated at 390°C for 2 hours under normal pressure in a nitrogen atmosphere. After the heat treatment, the mixture is cooled to room temperature to obtain heat-treated conductive particles. The average particle size of the conductive particles obtained is 3.22 μm, the thickness of the conductive layer is 110 nm, and the conductive layer has protrusions. In addition, the withstand current value of the conductive particles obtained is measured and the results are shown in Table 1.
[0189] [Table 1]
[0190] Average particle size (μm) Thickness of conductive layer (nm) Withstand current value (mA) Example 1 3.22 110 330.4 Example 2 3.22 110 288.9 Example 3 3.22 110 270.5 Comparative Example 1 3.22 110 85.4 Comparative Example 2 3.22 110 152.4 Comparative Example 3 3.22 110 193.2
[0191] According to the results in Table 1, it is determined that the conductive particles obtained in the examples have a high withstand current value.
[0192] [Evaluation of connection resistance and connection reliability]
[0193] Using the conductive particles of Examples and Comparative Examples, connection resistance and connection reliability were evaluated by the following methods.
[0194] 1.0 g of the conductive particles obtained in the examples and comparative examples were placed in a vertically erected resin cylinder with an inner diameter of 10 mm, and the resistance between the upper and lower electrodes was measured at room temperature (25°C · 50% RH) with a load of 2 kN applied to obtain the initial volume resistance value. The lower the initial volume resistance value, the lower the connection resistance of the conductive particles.
[0195] The resistance value after keeping for 24 hours at 85° C. and 85% RH was also measured. The smaller the difference from the connection resistance value at room temperature, the better the connection reliability of the conductive particles can be evaluated.
[0196] [Table 2]
[0197]
[0198] Based on the results, it was determined that the conductive particles obtained in the examples had lower initial volume resistance and lower connection resistance than the conductive particles obtained in the comparative examples. It was also determined that the conductive particles obtained in the examples had a smaller difference between the initial volume resistance and the resistance after being kept at 85°C·85%RH for 24 hours than the conductive particles obtained in the comparative examples, and had higher connection reliability. In particular, when the conductive particles obtained in Examples 1 and 2 were compared with the conductive particles obtained in Comparative Example 3, it was determined that conductive particles with low connection resistance and excellent connection reliability could be obtained by heating under vacuum.
Claims
1. A method for producing conductive particles, characterized in that: The method comprises heating the conductive particles having a conductive layer on the surface of the core particles at a temperature of 200 to 600° C. under a vacuum of 1000 Pa or less, The core particles are made of an organic material, or a material that includes both inorganic and organic materials. The conductive layer is one or a combination of two or more selected from gold, gold alloy, silver, copper, nickel, nickel alloy, palladium, rhodium or solder. The heating rate from room temperature to the heating temperature is 0.1 to 50° C. / min.
2. The method for producing conductive particles according to claim 1, wherein: The heating time is 0.1 to 10 hours.
3. The method for producing conductive particles according to claim 1 or 2, wherein: The cooling rate after heating is 0.02 to 50°C / min.
4. The method for producing conductive particles according to claim 1 or 2, wherein: The conductive particles are allowed to stand at a thickness of 0.1 to 100 mm and are heated.
5. The method for producing conductive particles according to claim 1 or 2, wherein: The conductive layer is at least one selected from nickel, gold, a nickel alloy and a gold alloy.
6. The method for producing conductive particles according to claim 1 or 2, wherein: The conductive layer is formed on the surface of the core particle by electroless plating, and the obtained conductive particles are heated.
7. A conductive particle, characterized in that: The conductive particles are produced by the production method according to any one of claims 1 to 6, In the conductive particles having the conductive layer formed on the surface of the core particle, the withstand current value of each conductive particle at a compression rate of 30% is 200 mA or more on average.
Citation Information
Patent Citations
Manufacture of plated material
JP1986064882A
Method and apparatus for testing electric characteristic of conductive fine particle
JP1998221388A
Method of producing two layer coat particulate powder, and two layer coat particle powder obtained by the production method
JP2005200728A
Conductive particle, method for producing conductive particle, conductive material and connection structure
JP2016167449A
Production of electrically conductive inorganic siliceous material
JP1988153280A